2020
DOI: 10.1111/1750-3841.15008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination conditions on enzyme activities and starch hydrolysis of long‐grain brown rice in relation to flour properties and bread qualities

Abstract: Gluten-free products from rice are gaining popularity because of its hypoallergenic characteristic. The absence of gluten results in inferior bread qualities such as hard texture, reduced volume, and shorter shelf-life. Hydrolytic enzymes are activated during germination to stimulate plant growth, and germinated brown rice (GBR) has been shown to improve gluten-free bread properties. However, the changes in hydrolytic enzyme activities under different germination conditions and their relationship with the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Moreover, Wunthunyarat et al . ( 5 ) also confirmed that during germination, by the actions of α-amylase, increased concentrations of saccharides with lower degrees of polymerization were observed.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, Wunthunyarat et al . ( 5 ) also confirmed that during germination, by the actions of α-amylase, increased concentrations of saccharides with lower degrees of polymerization were observed.…”
Section: Resultssupporting
confidence: 67%
“…Amongst various approaches introduced to increase brown rice acceptance, germination has been considered as the most suitable method to especially ameliorate brown rice sensory attributes, nutrient contents and functional compounds ( 5 , 6 ). Significant biochemical changes during germination lead to the increase in free amino acids, reducing sugars (due to the action of amylolytic enzymes), γ-aminobutyric acid (GABA) and soluble fibre content in germinated brown rice ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors worked on different varieties of wheat [12][13][14][15][16], whereas fewer studied mung beans, buckwheat, broccoli, radish, alfalfa, chickpeas, brown rice, etc. [1,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A speed of 1.7 mm/s was utilized for the MSSC strain to 40% of the initial state. Three slices (20 ± 2 mm thickness) obtained from the middle of MSSC were made for each measurement (Wunthunyarat, Seo, & Wang, 2020).…”
Section: Methodsmentioning
confidence: 99%